STARN, ORIN Y MIGUEL LA SERNA (2021), RIVERS OF BLOOD. RISE AND FALL OF THE SHINING PATH. LIMA: IEP - MARCELO DOROTEO, Raúl Cesar (2023)
This text, published by the Institute of Peruvian Studies (IEP), forms part of the Ideology and Politics series. In 21 chapters and an epilogue, it narrates the The rise and fall of the Shining Path, a party that took up arms early 1980s in the Central Andes.